1999
DOI: 10.1002/(sici)1097-4628(19990606)72:10<1249::aid-app3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed biocompatible membrane and effects of its smoother surface on antithrombogenicity

Abstract: ABSTRACT:The new biocompatible cellulosic membrane (AM-BC-F[AM-BIO-HX], Asahi-Medical Co. Ltd., Tokyo, Japan) has been developed, which has a higher flux than conventional membranes and more excellent antithrombogenicity because of its smoother membrane surface. The roughness of the inner surface of the AM-BC-F membrane was smaller than that of conventional membranes, as observed by Atomic Force Microscopy, because it was produced by the newly developed spinning method of cuprammonium cellulose solution, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The values in Table II for most of the cases indicate that the roughness increased initially with the addition of MSG. 34,35 The contact angles of the different membranes were found to predict the hydrophilic characteristics of the membranes. These roughness parameters with further increases of MSG started to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…The values in Table II for most of the cases indicate that the roughness increased initially with the addition of MSG. 34,35 The contact angles of the different membranes were found to predict the hydrophilic characteristics of the membranes. These roughness parameters with further increases of MSG started to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…It has been generally accepted that the surface roughness greatly affected the biocompatibility of materials. Fukuda et al46 demonstrated that a hemodialysis membrane with smoother inner surface possessed better hemocompatibility. Lee et al47 observed the effect of fiber diameter (surface curvature) on the growth behavior of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fractured membrane was soaked in ethanol, t ‐butanol/ethanol (50/50 vol %), and t ‐butanol successively for 30 min (two times) each to substitute alcohol for water in the membrane, and then it was freeze‐dried in vacuo for 3 days. The origin of this method was the one reported by Fukuda et al27 After platinum was spattered onto the dry membrane, the top surface and cross section of the membrane were observed with a scanning electron microscopy (SEM) instrument equipped with a field emission gun at an accelerated voltage of 3 kV (JSM‐840F, JEOL, Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%